Perbandingan Algoritma Elias Delta Code Dan Unary Coding Dalam Kompresi Citra Forensik - Michael Simangunsong (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Human needs in an image since long time ago is a need that cannot be ignored. Since the invention of the lat tool to capture an image like a camera. The rapid development of information technology has become a very important role for information exchange. This delivery speed is very dependent on the size of the information. One of the solutions to the above problem is to compress the data before it is transmitted and then the recipient will decompress that is reconstructing it back into the original data. Another problem is when we want to save the file. With a large size, the image file also requires a fairly large storage media In practice, compression techniques are divided into two, including lossy compression and lossless compression. Elias Delta Code is a breakthrough made by Piter Elias as a sophisticated algorithm that applies the Elias Gamma Code as the basis of the algorithm, while the Unary Coding algorithm is a method inspired by Neuroscience, where existing data is usually spatially coded, so the location shows where the data is located . This is done by marking certain slots. With the compression process, it is very helpful for humans in terms of sending data, saving storage media from the amount of data capacity stored.